Generative work: Day labourers' Freirean praxis. (August 2015) - Theodore, Nik
This paper examines an important aspect of the politicisation of contingent work: the evolution of grassroots organising strategies by immigrant day labourers, an allegedly 'unorganisable' class of contingent workers. The paper focuses on the ways in which repertoires of contestation – based in a philosophy of social transformation through radical democracy and Popular Education – have defused from mass-movement social struggles in Latin America in the 1980s to street-corner organising in US cities today. Through a series of in-depth interviews with day labour organisers, the paper: (1) follows the continental travels of Popular Education methodologies; and (2) explores how organising approaches from the global South have been adapted and recombined to meet the challenges presented by day labour markets in the US which are characterised by rampant violations of core labour standards.